2013
DOI: 10.1080/19942060.2013.11015490
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Flat Roofs Subjected to Non-Stationary Moving Microbursts

Abstract: This paper deals with the dynamic response of a flat roof which is subjected to a moving microburst. Taking the fluid-structure interaction into account, a methodology for the numerical simulation of the time histories of wind pressures on the roof is proposed by retrofitting the usage of deterministic-stochastic hybrid model. Whereby, the dynamic response of the roof could be computed. Gust-front factor, which is defined as the ratio of the maximum response caused by downburst to that caused by atmospheric bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…First, the multi-point method requires less computation and takes into account more detailed flight characteristics, as it requires solving the six-degree-of-freedom flight nonlinear equations of aircraft motion calculate the size and direction of the microburst in each element. Recent studies have only studied the effects of microbursts on fixed [42] [43] [44] or simple dynamic structures [45] using CFD methods. In addition, in CFD analysis, it is necessary to determine the trajectory of the aircraft in the microburst as a boundary condition.…”
Section: Multi-point Loading Modelmentioning
confidence: 99%
“…First, the multi-point method requires less computation and takes into account more detailed flight characteristics, as it requires solving the six-degree-of-freedom flight nonlinear equations of aircraft motion calculate the size and direction of the microburst in each element. Recent studies have only studied the effects of microbursts on fixed [42] [43] [44] or simple dynamic structures [45] using CFD methods. In addition, in CFD analysis, it is necessary to determine the trajectory of the aircraft in the microburst as a boundary condition.…”
Section: Multi-point Loading Modelmentioning
confidence: 99%
“…Therefore, additional studies have been performed particularly to gain a better understanding of the downburst-induced vibration responses of long-span roof structures. Through the use of an improved deterministic-stochastic hybrid model, Chen et al [24] presented a new method to numerically simulate the wind pressure and compute the microburst-induced response of a flat roof. They found that the ratio of the jet speed to translation speed of a microburst significantly influenced the peak value of the structural wind pressure.…”
Section: Introductionmentioning
confidence: 99%